On a Class of Schrödinger System Problem in Orlicz–Sobolev Spaces - H. El-Houari; L. S. Chadli; H. Moussa (Journal of Function Spaces)
Using the mountain pass theorem, we obtain the existence of a nontrivial and nonnegative weak solution of a quasi-linear Schrödinger system driven by the ω⋅-Laplacian operator in Orlicz–Sobolev spaces.